Breast Cancer Chemoprevention from Nano Zingiber officinale Roscoe - Wardana AP; Kristanti AN; Aminah NS; Fahmi MZ; Raoov M; Indriani (International Journal of Nanomedicine)
Andika Pramudya Wardana,1 Alfinda Novi Kristanti,2,3 Nanik Siti Aminah,2,3 Mochamad Zakki Fahmi,2 Muggundha Raoov,4 Indriani5 1Department of Chemistry, Faculty of Mathematics and Natural Science, Universitas Negeri Surabaya, Surabaya, East Java, Indonesia; 2Department of Chemistry, Faculty of Science and Technology, Universitas Airlangga, Surabaya, East Java, Indonesia; 3Biotechnology of Tropical Medicinal Plants Research Group, Universitas Airlangga, Surabaya, Surabaya, East Java, Indonesia; 4Department of Chemistry, Faculty of Science, University of Malaya, Kuala Lumpur, Malaysia; 5Department of Chemistry, Faculty of Mathematics and Natural Science, Universitas Tadulako, Palu, Central Sulawesi, IndonesiaCorrespondence: Alfinda Novi Kristanti, Department of Chemistry, Faculty of Science and Technology, Universitas Airlangga, Surabaya, East Java, Indonesia, Tel +62-31-5936501, Fax +62-31-5936502, Email alfinda-n-k@fst.unair.ac.idBackground: After cardiovascular disease, cancer is one of the leading causes of death due to uncontrolled cell growth. Breast cancer is among the most prevalent types of cancer. Zingiber officinale Roscoe. rich in phenolic compounds, which can stimulate and function as endogenous antioxidants.Purpose: Investigation of the in vivo chemopreventive has the potential of nano Z. officinale Roscoe (Zo-NPs) in breast cancer.Study Design: Using female Mus musculus Balb/c induced with benzo[α]pyrene, the chemopreventive action of Z. officinale Roscoe. nanoencapsulated using κ-carrageenan was assessed.Results: Z. officinale Roscoe Extract. contains 58 compounds, with the main component being [6]-gingerol with [6]-gingerol content being 697.65 ± 8.52 mg/g extract. Nanoencapsulation of Z. officinale Roscoe. has been successfully prepared with a particle size of 483.30 ± 11.23 nm. Zo-NPs are generally resistant to pH, temperature, and salt content variations. Compared to group C1, which underwent ductular dilatation, the administration of Zo-NPs (group T2) to female Mus musculus Balb/c, induced by benzo[α]pyrene, revealed no histological alterations in breast tissue. Moreover, administering Zo-NPs can raise blood serum levels of CAT, GSH, and SOD. In addition, it showed a greater ability to lower TNF-α levels than the T1 group, which received Z. officinale Roscoe extract. (Zo).Keywords: breast cancer, chemopreventive, nanoencapsulation, red ginger, Zingiber officinale Roscoe